Model Pemberdayaan Masyarakat Berbasis Peternakan Sapi Potong Kepemilikan Rakyat pada Wilayah Lahan Kering Sekitar Pinggiran Hutan (Studi Kasus pada Kampung Maslete, Kecamatan Kefamenanu, Kabupaten Timor Tengah Utara, Provinsi Nusa Tenggara Timur). - Sahala, Josua; Banu, Marselinus; Kadju, Fransiskus Yulius Dhewa; Chrisinta, Debora; Chamdi, Achmad Nur (Fakultas Pertanian, Universitas Timor, 2024)
This study aims to determine the potential for developing people's beef cattle farming business, to determine the livelihood capital assets of farmers including social capital, human capital, and physical capital, and the level of involvement and empowerment of farmers in the process of empowerment in dryland areas and to formulate an empowerment model in Maslete Village. This research was completed from July until August 2023 in Maslete Village, Kefamenanu District, North Central Timor Regency. The research used a purposive sampling method (intentionally) by taking all beef cattle breeders in Maslete village as many as 28 respondents. The data collection technique uses the Participatory Rural Appraisal (PRA) technique. Model formulation using Focus Group Discussion (FGD). The results showed that physical capital includes an assessment of the availability of medium production facilities (53.57%), an Assessment of the Availability and Ease of Access to medium educational facilities (67.86%), an Assessment of the status of livestock ownership, an assessment of good (100%), Assessment of inadequate communication facilities. good (12%) and the assessment of transportation facilities as poor (96.43%). Human capital includes an assessment of the level of education as poor (71.43%) and an assessment of the level of health as good (71.43%). Social Capital includes a moderate assessment of involvement in social organization activities (71.43%) and a good social network assessment (92.86%). The level of farmer empowerment includes moderate knowledge (75%), medium attitude (24%), and medium skills (82.14%). Community empowerment model with an integrated system on agricultural land, livestock, and land around the edge of the forest.